Investigation of binder removal, FTIR-based structural analysis, and reuse within the scope of the circular economy for rubber-based waste briquettes containing different types of binders using the alkali-oxidative recovery process - Topuz, Sibel; Tasar, Seyda (Elsevier, 2026)
Rubber waste, particularly end-of-life tires and industrial rubber residues, represents a significant environmental problem. In this study, the secondary recovery of rubber-based briquettes using an alkali-oxidative method and their reuse potential were investigated. The aim was to chemically remove binder phases such as polyurethane, epoxy, or bitumen while preserving the vulcanized rubber structure. The experimental process was conducted using NaOH-NaClO solutions at 70-80 degrees C in a continuously stirred system. FTIR analyses revealed that binderspecific peaks in the range of 1700-1300 cm- 1 decreased by up to 80%, while the characteristic bands of rubber (2850-2950 cm-1) were preserved. The material preserved its structural integrity, as indicated by FTIR analysis, suggesting that the elastomeric backbone was largely maintained. Accordingly, the recovered rubber material exhibits reprocessable characteristics and shows potential for reuse in applications such as re-briquetting, asphalt modification, concrete additives, vibration damping, and filtration materials. In conclusion, the alkali-oxidative process provides a low-cost, eco-friendly, and practical devulcanization approach. This study offers a sustainable pathway for the chemical recovery of waste rubber and its integration into the circular economy.
Keywords: Secondary recovery; Alkali-oxidative method; Rubber-based briquettes; Sustainability; Circular economy; FTIR characterization